(untitled) (Research, Society and Development, 2021)
Sepsis is a syndrome defined as a systemic and disordered response to a specific infectious condition, caused by any microorganism, presenting itself in different clinical stages of the same pathophysiological process. Early identification of sepsis is essential, in addition to the use of scales to quickly identify the affected organs in order to optimize the administration of certain hospital resources. The aim of this study is to investigate the association between Sequential Organ Failure Assessment (SOFA) scale scores and mortality of patients admitted to an intensive care unit. This is a prospective cohort study with document analysis. The respiratory and coagulation systems were not associated with mortality. However, the scores of the other 4 systems (hepatic, cardiovascular, neurological and renal) showed a strong association with mortality in the study sample (p-value <0.05). It was possible to show that the SOFA scale is a predictor of mortality associated with organ dysfunction in patients with infection, hospitalized in a intensive care unit.